2003
DOI: 10.1002/jbm.b.10051
|View full text |Cite
|
Sign up to set email alerts
|

A new model of implant‐related osteomyelitis in rats

Abstract: Infection related to osteosynthesis often has dramatic consequences for the patient. Prolonged hospitalization with systemic antibiotic therapy, several revision procedures, possible amputation, and even death may occur. To investigate the pathology of infection in orthopedic surgery, a new rat model of implant related osteomyelitis was developed. Three different concentrations (10(6), 10(3), and 10(2) colony-forming units (CFU)/10 microl) of Staphylococcus aureus were inoculated into the tibial medullary cavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
139
3
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(155 citation statements)
references
References 41 publications
11
139
3
2
Order By: Relevance
“…First, the field has been overly concerned with intramedullary implant models, since this represents the more serious clinical condition. [8][9][10][11][12][13] Unfortunately, we found that this IMPLANT-ASSOCIATED OSTEOMYELITIS model gave rise to highly variable (temporal and spatial) lesions, making a reproducible, quantitative model very challenging, although others have recently succeeded. 24 In contrast, we have found that implantation of an infected transcortical pin always produces lesions adjacent to the pin, and never results in distal OM, hematogenous infection, or death (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the field has been overly concerned with intramedullary implant models, since this represents the more serious clinical condition. [8][9][10][11][12][13] Unfortunately, we found that this IMPLANT-ASSOCIATED OSTEOMYELITIS model gave rise to highly variable (temporal and spatial) lesions, making a reproducible, quantitative model very challenging, although others have recently succeeded. 24 In contrast, we have found that implantation of an infected transcortical pin always produces lesions adjacent to the pin, and never results in distal OM, hematogenous infection, or death (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As such, biofilm biology, which plays a critical role in resistance of chronic OM to antibiotic therapy by serving as a dominant protective barrier from the action of antibiotics, can only be studied with in vivo models. 4 To date, much of our knowledge of the pathogenesis of OM comes from animal models, 5 which have existed in chicken, 6 rat, 7,8 guinea pig, 9 rabbit, 10 dog, 11 sheep, 12 goat, 13 and most recently mouse. 14 While these models have been used to confirm the importance of bacterial adhesions identified from in vitro assays, [15][16][17] none of them contain quantitative endpoints that can determine bacterial load or growth in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In histological evaluation, the results were consistent, although two specimens in each group were evaluated [15]. The callus tissues of both groups at the third week were similar, but at the sixth week, the callus formation remained immature in the infection group.…”
Section: Discussionmentioning
confidence: 58%
“…Torque to failure and stiffness both were lower in the infection group than in the control group at 6 weeks, but with the numbers available for testing, they were not different at 3 weeks (p = 0.615 and p = 1, respectively; Table 2 [3][4][5][6][7][8][9][10][11][12][13][14][15][16]; p = 0.004) both were greater in the control group than in the group with infection. Maximum torque to failure was lower in the infection group than in the control group at all time points.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation